The relationship between trade policies and macroeconomic adjustments in the Russian cheese market integration - Alisher Tleubayev; Tinoush Jamali Jaghdani; Linde Götz; Miranda Svanidze (Journal of New Economy, 2021)
Many different events happened in 2014 that affected Russia's domestic markets. Among different dairy products, cheese has been the one for which domestic production has significantly increased and cheese import decreased since the summer of 2014. This paper aims to explore the effects of trade policies and other macroeconomic changes in 2014 on cheese price development in the domestic Russian market. Based on the law of one price, we considered price cointegration and price dispersion methodologies to test the cheese prices developments between producing and consuming regions before and after the summer of 2014. We applied Johansen co-integration test, VECM and dynamic panel models. We used 39 price pairs between main cheese producing and cheese consuming regions for the period of 2008–2016 for price cointegration and partially for price dispersion. The research results show that cointegration of cheese prices between producing and consuming regions have substantially increased since the summer of 2014. Moreover, the dispersion of cheese prices between Moscow and the cheese producing regions has increased with significant effects of counter-sanctions, a reduction in cheese imports, and devaluation of the Russian currency. We conclude that the market efficiency has not increased in spite of boosted domestic cheese trade.
Keywords: Q12; Q17; O18; 630; trade policy; market efficiency; counter-sanctions; cointegration; price transmission; price dispersion; cheese market; Russia